The Use of Learners’ "One Night Speed System" Studying Methods on English Lesson - Sholatingratri, Aulia Inayah; Nagara, Graena Pelangi (ICONELT, 2022)
One Night Speed System (ONSS) is the only a model of study method to complete any task in one night. Meanwhile, the expert stated that the distance between learners’ study time should be in accordance with what is the response to understanding school material. This study was made to find out the answer to whether there is an effect of ONSS on learning outcomes, especially English. This research was conducted specifically for the student population in Indonesia which is limited to 71 (18 males and 53 female) learners from various levels of education. This study uses a descriptive quantitative approach. data analysis using logistic regression analysis method. Based on the questionnaire, it was found that most of the learners thought that there was success from the application of the ONSS learning method in understanding English material. The results showed that there was success in understanding English lessons in the use of ONSS to learn English without an impact on the decline in grades. Even so, the understanding of the material obtained is not optimal and has more impact on learners’ health problems.